DAMPAK BAYI TABUNG PADA MASA TRADISIONAL DALAM KONSEP PENCIPTAAN HIDUP - Ivana Shirley Lafayette Siregar; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
IVF technology has become one of the leading innovations in the field of human reproduction, providing new hope for couples experiencing difficulties with natural conception. However, its impact is not limited to medical aspects alone, but also includes complex social, cultural and ethical implications. This article explains the influence of IVF technology on social norms, responses from religious circles, implications for family identity, ethical conflicts that arise, increased opportunities for infertile couples, negative responses from traditional societies, and the relationship between science and morality. By understanding the moral and ethical implications and raising public awareness, we can manage the development of IVF technology wisely, ensuring that its use benefits overall human welfare, while remaining mindful of the moral and ethical values ​​that underlie our existence as a society. The world continues to experience development with the emergence of various new technologies in every sector of life. This development is often triggered by the emergence of human problems that occur from time to time. As stated by Dixon, changes in the economic and social fields often encourage the emergence of technological innovations that can overcome existing problems.